MY SAY: Innovators, imitators and idiots - Abd Razak, Dzulkifli (2008)
The current financial crisis can be explained by the involvement of three groups that begin with "i": namely, "the innovators", "the imitators" and "the idiots", I heard at a seminar recently. While one can reasonably guess who should be in the first two groups, it is not so easy to pinpoint who belongs to the third. Going by a recent statement issued by former Federal Reserve chairman Alan Greenspan, whom some regard as one of the "innovators" (or even "the maestro"), there are ample indications as to who they are. In USA Today, he reportedly admitted that he trusted the banks and investment houses not to do stupid and destructive things, and was stunned when he found that was exactly what they were doing. Until the dust settles, the jury is still out on whether they are the real idiots!